Revision of Stenetra Masi, 1931 (Hymenoptera: Chalcidoidea: Pteromalidae) - Tselikh, Ekaterina; Burks, Roger (Zootaxa, 2020)
The species of Stenetra Masi (Hymenoptera: Pteromalidae) are revised. Nine world species are recognized based on females, of which seven new species are described: S. californica Tselikh & Burks sp. nov. (USA), S. caucasica Tselikh sp. nov. (Armenia, Georgia), S. daleskeyae Tselikh sp. nov. (Kazakhstan, Russia, Spain), S. khalaimi Tselikh sp. nov. (Israel), S. longuncus Tselikh & Burks sp. nov. (USA), S. miyazakii Tselikh & Burks sp. nov. (Canada), S. parvula Tselikh & Burks sp. nov. (USA, Mexico). With the description of new species, Stenetra is for the first time recorded from the New World and Nearctic region. All the species are described or redescribed and illustrated by macrophotography, including type material of previously described species, and a key for the identification of the nine known species is given.